PREVALENCE OF ANEMIA IN STUDENTS OF NOWSHERA MEDICAL COLLEGE: A CROSS-SECTIONAL STUDY FROM NOWSHERA - Dr. Muhammad Zahid; Dr. Alamzeb Jadoon; Dr. Syeda Khadija Mahrukh; Dr. Durre Shehwar; Dr. Atif ullah; Dr. Afshan Ali (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: To determine the prevalence of anemia in young students aged 17-24 years at Nowshera Medical College, Nowshera Materials and Methods: The study design was a cross-sectional, descriptive study conducted in the Department of Physiology, Nowshera Medical College, Nowshera from June 2019 to November 2019. The participants were recruited in the study through random, consecutive sampling. Total 124 students of Nowshera Medical College; Nowshera aged 17-24 years. After obtaining informed consent; the participants were subjected to measurement of height, weight, BMI, and venous blood sampling for estimation of Hemoglobin level for diagnosis of anemia as per WHO criteria. Results: The mean hemoglobin concentration of 14.59 gm/dL. Of the total 124 participants, 7.3 % (n=9) were found to be anemic. Anemia was comparatively more prevalent in females and the anemic students had a comparatively lower mean BMI as compared to non-anemic participants but the correlation between anemia, gender, and body mass index was statistically insignificant. Conclusion: The prevalence of anemia was only 7.3 %, in sharp contrast to expectations and no statistically significant difference was noted among genders.